HOW TO TRANSLATE SCIENTIFICALLY: A CASE IN THE JOURNAL OF “MEDICINA” - Juliarta, I Made (Lingual Journal of Language and Culture; Vol 1 No 1 (2016)DO - 10.24843/LJLC.2016.v01.i01.p06, 2016)
This reasearch aimed at analyzing and discussing the technique or procedure applied by translator in translating text found in the journal medicina. There are some procedures of translation techniques found and applied by translator. Some of the translation techniques applied by the translator consisting of borrowing, transposition, equivalence, structure shift, unti shift, literal, calque, addition and substraction. It was the borrowing technique used in applying the translation of terms which have been considered a part of respective TL. Unit shift is said as the change from word to group of word or in reverse. A different of modifierhead rule between SL and TL can occur in the structure shift. Equivalence and literal translation or words per word translation were found. It is important to apply the technique of calque which was reagarded as special kind of borrowing. There were the last two techniques which were also found as unavoidably which is applied by translator. Applying appropriate techniques in translating is needed in order the translation product can be reliable and acceptable for the reader.
Keywords: source language, target language, techniques of translation